2011
DOI: 10.1038/ijo.2011.101
|View full text |Cite
|
Sign up to set email alerts
|

Type I iodothyronine 5′-deiodinase mRNA and activity is increased in adipose tissue of obese subjects

Abstract: Differentiation and metabolism of adipose tissue are modulated by thyroid hormones (THs), but relatively little is known about the metabolism of THs in this tissue. Expression of the genes for type I iodothyronine 5 0 -deiodinase (D1), leptin (LEP) and stearoyl-CoA desaturase 1 (SCD-1) was evaluated in omental (OM) and subcutaneous (SC) fat using a cohort of 70 humans. Activities of iodothyronine deiodinases (D1, D2 and D3) were assessed in a randomly selected subpopulation of 19 subjects. D1 expression was up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…Similarly to our findings, an independent positive correlation between waist circumference and fT3 levels has been reported in obese women [19]. This result may be explained by the recent findings of Ortega et al [20], who demonstrated that the expression and activity of type I iodiothyronine 5′-deiodinase, an important source of circulating T 3 , are increased in adipose tissue from obese individuals.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly to our findings, an independent positive correlation between waist circumference and fT3 levels has been reported in obese women [19]. This result may be explained by the recent findings of Ortega et al [20], who demonstrated that the expression and activity of type I iodiothyronine 5′-deiodinase, an important source of circulating T 3 , are increased in adipose tissue from obese individuals.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, BAT depends on deiodinase activity but on subtype DII which in fasted conditions is dramatically upregulated. This regulation is critically dependent on the current thyroid status [22,36]. Studies in deiodinase knock-out (DII KO) animals support such notion.…”
Section: Thyroid and Energy Regulation: Pathophysiological Consideratmentioning
confidence: 72%
“…Indeed, under conditions of increasing adiposity, a higher DIO1 activity in white adipose tissue, through stimulation by leptin has been shown in mice (45). Also in humans, Ortega et al have shown an increase in DIO1-activity in hypertrophic white adipose tissue (46).…”
Section: Page 13 Of 31mentioning
confidence: 98%